2018
DOI: 10.26434/chemrxiv.6796181.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grand-Canonical Approach to Density Functional Theory of Electrocatalytic Systems: Thermodynamics of Solid-Liquid Interfaces at Constant Ion and Electrode Potentials

Abstract: Properties of solid-liquid interfaces are of immense importance for electrocatalytic and electrochemical systems but modelling such interfaces at the atomic level presents a serious challenge and approaches beyond standard methodologies are needed. An atomistic computational scheme needs treat at least part of the system quantum mechanically to include adsorption and reactions while the entire system is in thermal equilibrium. The experimentally relevant macroscopic control variables are temperature, electrode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…For oxygen and hydrogen, standard cavity radii 64 were used but for Au a larger radius of 2.0 Å was adapted based on our previous results. 65 The Au lattice constant was calculated to be 4.142 Å, which agrees well with the experimental value (4.065 Å 66 ). An Au(111) surface was selected to model the electrode surface as it is the most stable and abundant Au surface.…”
Section: Computational Detailssupporting
confidence: 82%
See 1 more Smart Citation
“…For oxygen and hydrogen, standard cavity radii 64 were used but for Au a larger radius of 2.0 Å was adapted based on our previous results. 65 The Au lattice constant was calculated to be 4.142 Å, which agrees well with the experimental value (4.065 Å 66 ). An Au(111) surface was selected to model the electrode surface as it is the most stable and abundant Au surface.…”
Section: Computational Detailssupporting
confidence: 82%
“…While we did not explicitly address the potential-dependent kinetics, we confirmed that the Fermi-levels coincide well with the experimentally relevant potential range of 0.6-1.0 V vs. RHE (henceforth referred as V RHE ). The Fermi-levels correspond to absolute electrode potentials, 65 and can be converted to the RHE scale by U (RHE) = −e(E F + 4.4eV ). The Fermi-levels (electrode potentials vs. RHE) are -4.9 eV (0.5 V), -4.8 eV (0.4 V), -4.8 eV (0.4 V), and -4.9 eV (0.5V) for the bare Au surface, GLY adsorption, neutral/acidic NEB calculations, and alkaline NEB calculations, respectively.…”
Section: Computation Of Adsorption Activation and Electrochemical Frmentioning
confidence: 99%
“…This interfacial water geometry has been shown to be the most stable geometry for protonated, that is, acidic water bilayers, at the potentials of interest for HER. 47,[53][54][55] The reaction pathways are all performed at constant potential within a tolerance of 0.01 V, and the relevant energy comparison is therefore the energy at constant potential (often referred to as Ω [38][39][40][41][44][45][46][47][48][49]56 ),…”
Section: Methodsmentioning
confidence: 99%
“…The advent of grand-canonical electronic structure schemes has allowed for explicit control of applied potential in atomistic studies of electrocatalytic systems by varying the number of electrons, allowing the workfunction to be tuned relative to some reference potential. [38][39][40][41][42][43][44][45][46][47][48][49] These methods provide a straightforward way of calculating reaction barriers at constant potential. In particular, the solvated jellium (SJ) method 47 accomplishes potential control for periodic systems by employing a counter charge in a solvated jellium slab, which localizes the excess charge on the reactive side of the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…45 To better understand the details of HER the electrified MoS 2 interface immersed in the electrolyte solution needs to be simulated. We herein apply the computationally efficient grand-canonical DFT approach [46][47][48] and investigate the competition with adsorption of the water solvent. In contrast to the computational hydrogen electrode (CHE) method, 49 grandcanonicl DFT allows to explicitly take the polarization of the electrode into account, thus going beyond the purely thermodynamic effects of the electrochemical potential on the energy of proton/electron pairs.…”
Section: Introductionmentioning
confidence: 99%